Analisis Efek Ramadhan Terhadap Abnormal Return dan Trading Volume Activity pada Perusahaan Yang Masuk dalam Jakarta Islamic Index (JII) di Bursa Efek Indonesia Periode 2014-2018 - Ahmad Faih; Rohmatun Nafiah (Al-Tijary, 2019)
This study is a study of events aimed at knowing the effects of Ramadhan, to companies listed on the Jakarta Islamic Index on the Indonesia Stock Exchange period 2014-2018, using abnormal return and trading volume activity indicators. This study uses secondary data in the form of daily stock price index for the period 2014-2018 , Composite Stock Price Index (IHSG) and trading volume, with the population of companies entering the Jakarta Islamic Index on The Indonesian Stock Exchange , The statistical test used to test the hypothesis is the normality test, and the paired sample t-test. Result of T-test on Abnormal Return between year 2014-2018 know that there is no significant influence between Ramadhan month to abnormal return from year 2014 until 2018. While for T-test on trading volume activity between year 2014 until 2018 know that only in 2014, 2015, and 2017, 2018 there are significant influence which means the market responds to the event. The result of the test of Ramadhan event has the information even though it does not happen in every year of the research period, this is because Ramadhan is a routine event occuring in Indonesia so investors have been able to predict how the stock movemonts in Indonesia Stock Exchange.